The degree of first-grade students’ possession of health experiences A field study from the point of view of the teachers in Lattakia City - هلّول شروق; مطيعة أحمد (Latakia University Journal - Arts and Humanities Sciences Series, 2023)
The aim of the current research is to identify the degree of first-grade students’ possession of healthy experiences in the city of Lattakia from the point of view of the teachers, and the research also aimed at identifying the differences in the degree of possession of healthy experiences according to the variables of experience and scientific qualification. The research Sample reached (208) male and female teachers who were completed. To reach the objectives of the research a questionnaire consisting of (24) items which is a list of healthy experiences was divided into three axes: (The experience of safety and maintaining the integrity of the body, Personal health experience, School hygiene experience), validated and stable, and the data were processed using the computer statistical software (SPSS). The results confirmed that the degree of possession of healthy experiences for first grade students came to a medium degree and was in the following order: (The experience of personal health, safety and maintaining the integrity of the body experience, School hygiene experience), and the results showed: _ There are no differences between the average scores of the research sample members about their estimation of possession of healthy experiences among first-grade students according to the variable number of years of experience. _ There are differences between the average scores of the research sample members about their estimation of possession of healthy experiences among first-grade students according to the academic and educational qualifications variable in favor of the educational qualification diploma holders.